1997
DOI: 10.1080/10601329708014989
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Substituents on the Radical Copolymerization of Ring-Substituted Methyl 2-Cyano-3-Phenyl-2-Propenoates with Styrene

Abstract: Copolymerizations of ring-substituted methyl 2-cyano-3-phenyl-2-propenoates, RC,H,CH=C(CN)CO,CH, (R = CtH5, CH30, C1, Br, F) with styrene (M,) were studied in solution in the presence of a radical initiator. Terminal and penultimate kinetic models were applied for best prediction of the copolymer composition. The Alfrey-Price Q and e parameters calculated for the monomers correlate well with the relative reactivity ( l/rl). The relative reactivity showed a tendency to increase with increasing Hammett constant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The conversion of the copolymers was kept between 10 and 20% to minimize compositional drift (Table 1). Nitrogen elemental analysis showed that between 19.4 and 30.0 mol% of MEPA is present in the copolymers prepared at ST/MEPA = 3 (mol), which is indicative of relatively high reactivity of the MEPA monomers towards ST radical which is typical of alkoxy ring-substituted phenylcyanoacrylates [18][19][20][21][22]. Since MEPA monomers do not homopolymerize, the most likely structure of the copolymers would be isolated MEPA monomer units alternating with short ST sequences (Scheme 2).…”
Section: Synthesis and Characterization Of Styrene -Mepa Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion of the copolymers was kept between 10 and 20% to minimize compositional drift (Table 1). Nitrogen elemental analysis showed that between 19.4 and 30.0 mol% of MEPA is present in the copolymers prepared at ST/MEPA = 3 (mol), which is indicative of relatively high reactivity of the MEPA monomers towards ST radical which is typical of alkoxy ring-substituted phenylcyanoacrylates [18][19][20][21][22]. Since MEPA monomers do not homopolymerize, the most likely structure of the copolymers would be isolated MEPA monomer units alternating with short ST sequences (Scheme 2).…”
Section: Synthesis and Characterization Of Styrene -Mepa Copolymersmentioning
confidence: 99%
“…Earlier we have reported synthesis and styrene copolymerization a number of alkoxy ring-substituted PCAs, such esters as methyl [18], ethyl [19], propyl [20], isopropyl [21], and butyl [22].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier we have reported synthesis and styrene copolymerization a number of alkoxy ringsubstituted PCAs, such esters as methyl [12], ethyl [13], propyl [14], isopropyl [15], butyl [16], and tert-butyl [17].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, copolymerization of electrophylic TSE monomers having double bonds substituted with halo, cyano, and carbonyl groups and electron-rich monosubstituted ethylenes such as styrene, N-vinylcarbazole, and vinyl acetate [13][14][15] show a tendency toward the formation of alternating copolymers -thus suggesting a way of functionalization of commercial polymers via introduction of isolated monomer units in copolymers. Earlier we have reported synthesis and styrene copolymerization a number of alkoxy ring-substituted PCAs, such esters as methyl [16], ethyl [17], propyl [18], isopropyl [19], and butyl [20].…”
Section: Introductionmentioning
confidence: 99%